Adipose tissue-secreted Spz5 promotes distal tumor progression via Toll-6-mediated Hh pathway activation in Drosophila. - Kong, D.; Li, X.; Zhao, S.; Wang, C.; Cai, Z.; Song, S.; Guo, Y.; Kuang, X.; Wang, X.; Liu, W.; Liu, P.; Guo, X.; et al. (The EMBO Journal, 2025)
Interorgan communication is vital for tissue homeostasis and health in multicellular organisms, and its disruption can lead to diseases such as cancer. Adipose tissue acts as a key endocrine center, secreting cytokines that influence remote organs. Despite clear links between obesity and increased cancer risk, the underlying mechanisms are unclear. Here, utilizing a Drosophila genetic model combining Gal4-UAS and QF-QUAS tissue-specific transgene expression systems, we reveal that adipose-secreted Spz5 ligand promotes distal epithelial tumor overgrowth and invasion. Mechanistically, Spz5 binds to tumor cell Toll-6 receptors, triggering the degradation of the endocytic adaptor protein AP-2? via Mib1-mediated ubiquitination. Consequently, impaired endocytosis leads to Smoothened (Smo) accumulation on the cell membrane and subsequent activation of the Hedgehog (Hh) pathway. This abnormal Hh activation synergizes with the oncogenic Yorkie (Yki) to drive tumor growth and invasion. Furthermore, tumor-derived Unpaired ligands (Upds) activate the JAK-STAT pathway in the fat bodies, which leads to Hippo pathway-dependent upregulation of spz5 expression. Thus, our study provides insights into the complex regulatory mechanisms by which systemic interorgan communication influences tumor progression.